COMPARATIVE EFFECTS OF STANDING AND CROUCHING POINTING ON PETANQUE ATHLETES’ 7-METER SKILLS - Dian Hamsari Hale; Susi Yundarwati; Edi Kurniawan (Universitas Pendidikan Mandalika, 2026)
This study aimed to examine the effects of standing pointing and crouching pointing training on 7-meter pointing skills in Petanque athletes of Pelatda Mataram City in 2026. Petanque is a precision sport in which pointing accuracy plays a decisive role in scoring and tactical performance, so identifying effective training techniques is important for athlete development. The study employed a quantitative quasi-experimental approach with a within-subject repeated-measures design. Twelve active athletes were selected using total sampling and were tested under two training conditions, namely standing pointing and crouching pointing. Data were collected through a standardized 7-meter pointing skill test using a scoring-zone system, then analyzed descriptively and inferentially through the Shapiro–Wilk normality test, Levene’s homogeneity test, and paired sample t-test, supported by effect size analysis using Cohen’s d. The findings showed that both training techniques significantly improved pointing performance. In the standing pointing condition, the mean score increased from 16.50 to 21.50, with t(11) = -9.319, p < 0.001, and Cohen’s d = -2.690. In the crouching pointing condition, the mean score increased from 15.67 to 22.42, with t(11) = -7.745, p < 0.001, and Cohen’s d = -2.236. Although crouching pointing produced a greater mean increase, standing pointing demonstrated a stronger practical effect. In conclusion, both techniques were effective in improving 7-meter pointing skills, but standing pointing showed a more dominant overall effect and can be prioritized in technical training programs for Petanque athletes.